2009
DOI: 10.1007/s00330-009-1667-0
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of pulmonary nodules on energy-subtracted chest radiographs with a commercial computer-aided diagnosis software: comparison with human observers

Abstract: Improved detection of pulmonary nodules on energy-subtracted chest radiographs with a commercial computer-aided diagnosis software: comparison with human observers Abstract Objective: To retrospectively analyze the performance of a commercial computer-aided diagnosis (CAD) software in the detection of pulmonary nodules in original and energy-subtracted (ES) chest radiographs. Methods: Original and ES chest radiographs of 58 patients with 105 pulmonary nodules measuring 5-30 mm and images of 25 control subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
1
11
2
1
Order By: Relevance
“…However, Balkman et al [15] found more nodules when CAD was combined with dual-energy subtraction radiography instead of conventional chest radiography. The FP rate of 1.27 per image with the CAD program on chest radiography was notably lower in our collective than reported in former studies, which ranged from 2.14 to 5.9 FPs per image [11,14].…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…However, Balkman et al [15] found more nodules when CAD was combined with dual-energy subtraction radiography instead of conventional chest radiography. The FP rate of 1.27 per image with the CAD program on chest radiography was notably lower in our collective than reported in former studies, which ranged from 2.14 to 5.9 FPs per image [11,14].…”
Section: Discussioncontrasting
confidence: 80%
“…The fact that the combination of dual-energy subtraction with CAD failed to improve the nodule detection rate is consonant with former results [14]. However, Balkman et al [15] found more nodules when CAD was combined with dual-energy subtraction radiography instead of conventional chest radiography.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…While previous research had evaluated the use of CAD and either hardware-or software-based methods separately, the two methods of bone suppressed image generation had not been directly compared. The results of this study suggest that the number of ROI and FPPI has been dramatically reduced from earlier versions of CAD used in conjunction with DESR [11,12,14] and also when compared to earlier software-based methods of bone suppression [13]. Additionally, sensitivity and specificity were found to be improved over previous versions evaluated in the literature [11,13,14].…”
Section: Discussionmentioning
confidence: 72%
“…Other authors, [10][11][12] indicated that hardware-based bone suppression (DESR) removed the presence of bony structures in digital chest radiographs and significantly improved the sensitivity of CAD performance in pathology-proven cases with pulmonary nodules while reducing the false-positive rate. Similarly, Freedman et al [13] suggested that softwarebased removal of bony structures also improved the rate of lung cancer detection.…”
Section: Introductionmentioning
confidence: 99%